The Effect of the Complementary Enzyme Q10 in Improving Some Functional Variables of Disabled Basketball Players - Sahar Hur Majeed (Journal of Global Pharma Technology, 2018)
Basketball for disabled players is regarded as a game that requires many functions, and this is attributed to the nature of the game itself that forces the disabled player to do moves recognized with high strength and special tempo in a short time. Therefore, the functional side is regarded as one of the fundamental demands for the occurrence of the necessary functional adaptations that might differ in degree from other sport games, and this is done through studying the biological variables because they are important and necessary since they have a great effect on the athletic performance and the physical capacities that are essential for the basketball game in general, and basketball for disabled players in particular because of its great importance in the basketball match especially they, functional variables, occur under the anaerobic  lactic system where the player should have the ability to do his skills in a high speed and frequently in the match. The research aims at preparing anaerobic exercises through taking the Q10 enzyme to improve some of the functional variables of the disabled basketball players. The research also aims to identify the effects of the anaerobic exercises by taking Q10 enzyme, the experimental method was used by taking the Iraqi disabled basketball team as a specimen. 18 players were divided randomly into three groups (experimental 1, experimental 2, and control group) each group consisted of 6 players. The (experimental 1) group had to do the anaerobic exercises prepared by the researchers with doses of the coenzyme Q10; (experimental 2) group had to do anaerobic exercises prepared by the researchers, whereas the (control) group had to do special exercises. Based on the above plan, the coenzyme was used as capsules (100 mg.) taken daily before breakfast, the total enzyme dosage becomes (60 gm.) equivalent to (3gm.). The study concluded that exercises with the use of the complementary Q10 enzyme lead to improve heartbeat ratio before and after exertion, as well as improve the level of lactic acid before and after exertion. Furthermore, it improved the level of V2 Max of the research specimen.Keywords: Enzyme, Functional Variables and Basketball.